Exploring Trends and Barriers to Physical Activity in Adolescents/ School Going Children of Rawalpindi: Trends and Barriers to Physical Activity - Diba, Farah; Shaheen, Dure Yakta; Habib, Muhammad Farrukh; Raisani, Sher Afgan; Khan, Javeria; Rehman, Atta Ur; Faiz, Sajida; Yasmin, Rehana; Noreen, Mehmoona; Nazeer, Nazma (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2023)
Adolescent’s active participation in PA may reduce the risk of chronic non-communicable diseases (NCDs) in adulthood. Barriers to PA and the association among these barriers were examined. Objective: To explore barriers to PA in the adolescent of public school of Rawalpindi, Pakistan. Methods: A Descriptive cross-sectional design, multistage cluster sample of adolescents (N = 400) with 214 (53.5%) male and 186 (46.5%) females was conducted. Independent variables such as sociodemographic, (i.e., education, age, gender, socioeconomic level), the discernment of barriers which did not permit to take part in PA, (i.e., fear of harm, lack of time, resources, social support, energy, and motivation, inaccessibility of recreational sports near residence and lacking skills); and adolescent’s physical activity participation was evaluated using WHO tool, international physical activity questionnaire (IPAQ). To investigate the connection between perceived barriers and PA participation, multiple regression analysis was used. Results: Of the 400 adolescents females are more likely to perceive a lack of time as a barrier to engaging in PA [OR 2.17 (95% CI (1.45—3.23)]. In a similar vein, those from lower socioeconomic levels are more likely to perceive a lack of motivation. [OR 2.17 (95% CI (1.42—3.32]. Regarding poor /fair Self-perception of health have a high chance of perceiving scarcity of resource [OR 4.25 (95% CI (2.72—7.43)] were viewed as obstacles to PA. Conclusions: Low socioeconomic status, lack and standard of education, and self-perception of health are indicators of are indicators of potential obstacles to physical activity